A sensitive and robust method for the determination of alkylphenol polyethoxylates and their carboxylic acids and their transformation in a trickling filter wastewater treatment plant. - Koh, Yoong K. K.; Chiu, Tze Y.; Boobis, Alan R.; Cartmell, Elise; Pollard, Simon J. T.; Scrimshaw, Mark D.; Lester, John N. (Elsevier Science B.V., Amsterdam., 2008)
This paper presents a method for the determination of alkylphenols, alkylphenol polyethoxylates (APEO) and alkylphenol ethoxycarboxylates (APEC) in the aqueous and particulate phase of wastewater samples. Quantification was achieved by liquid chromatography-tandem mass spectrometry. The sensitivity of the method is demonstrated by low detection limits, in the dissolved phase 1.2–9.6 ng l−1 for alkylphenol, AP1–3EO and APEC and 0.1–4.1 ng l−1 for longer chain alkylphenol polyethoxylates. The method detection limit for particulate phase samples ranged from 6 to 60 ng g−1 for AP, AP1–3EO and APEC; with the longer chain APEO being from 0.5 to 20 ng g−1. Matrix effects were noted in complex matrix rich samples. There was a distinct change in the distribution of alkylphenol ethoxylates during biological treatment of the wastewater, with the major biotransformation products observed being carboxylated derivatives at concentrations of up to 1768 ng l−1. Shorter chain APEO were present in higher proportions in the suspended solids, due to their higher affinity to particulate matter compared to the lon
Keywords: Alkylphenol; Polyethoxylates; Carboxylates; Dissolved; Particulate